The Merror - Wong, Andrew Su Jun (2019)
Memes are jokes in the form of pictures or videos that spread from person to person on the Internet, and are commonly expressed as text overlaid over funny pictures. They are an excellent tool of communication and have come a long way from being silly jokes passed around on the Internet. They are now used to communicate information about more substantial issues like current affairs and in some instances even serve as a commentary on society and the world at large. Memes play a big role in today’s online culture, and its influence on public perception will continue to grow due to a few reasons: a preference for more non-verbal forms of communication and changing behavioural patterns on social media. My project acts as a commentary on the large amount of information communicated through memes today, and seeks to get young adults to be more discerning about the information found in memes. How much can we trust information that is communicated through anonymously created memes, and how effective are they at providing information with suitable context? Are they only suitable for expressing personal jokes/stories, or can they be used to communicate about more serious issues? I seek to do this through a fictional news company called The Merror, which communicates news solely through memes. The Merror, through its website and newspapers, invites viewers to openly consider a world where memes are used to communicate arguably the most important information we have: news.